2021
DOI: 10.1038/s43247-021-00130-w
|View full text |Cite
|
Sign up to set email alerts
|

Past megadroughts in central Europe were longer, more severe and less warm than modern droughts

Abstract: Megadroughts are notable manifestations of the American Southwest, but not so much of the European climate. By using long-term hydrological and meteorological observations, as well as paleoclimate reconstructions, here we show that central Europe has experienced much longer and severe droughts during the Spörer Minimum (~AD 1400–1480) and Dalton Minimum (~AD 1770–1840), than the ones observed during the 21st century. These two megadroughts appear to be linked with a cold state of the North Atlantic Ocean and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 59 publications
0
36
1
Order By: Relevance
“…Another possible field of application is palaeoclimatology. Spatial distribution of precipitation extremes is known to have changed markedly in the past Ionita et al, 2021b), and clustering based on climate models could be used to generalise the sparse existing data to larger regions.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible field of application is palaeoclimatology. Spatial distribution of precipitation extremes is known to have changed markedly in the past Ionita et al, 2021b), and clustering based on climate models could be used to generalise the sparse existing data to larger regions.…”
Section: Discussionmentioning
confidence: 99%
“…A series of dry years has been observed within Eastern Europe and Western Russia (EE/WR) over the last 15 years (e.g., [11]). Ionita et al [11] demonstrated past 'megadrought epochs' over central Europe were decadal.…”
Section: Introductionmentioning
confidence: 99%
“…A series of dry years has been observed within Eastern Europe and Western Russia (EE/WR) over the last 15 years (e.g., [11]). Ionita et al [11] demonstrated past 'megadrought epochs' over central Europe were decadal. However, [12] found the trend in drought over central and eastern Europe has been steady since the mid-20th century.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme drought in 2018 severely affected forest stands in Germany (Ionita et al., 2021), and, as a consequence, about twice as many trees died in 2019 compared to 2018 and about 80% of all living trees showed poor vitality (BMEL, 2020). Climate conditions, which are currently perceived as extreme (Büntgen et al., 2021), could represent the new ‘normal’ in the near future (Hari et al., 2020; Scharnweber et al., 2020).…”
Section: Introductionmentioning
confidence: 99%